Peningkatan Pengetahuan pada Kader Posyandu tentang Imunisasi di Kecamatan Ulubelu, Tanggamus, Lampung - Alvin Widya Ananda; Fitria Saftarina; Betta Kurniawan; Dian Isti Angraini (Majority, 2020)
The coverage of infant immunization in 2017 in Lampung province in the form of BCG immunization was 99.88%, DPT1 was 100% and measles was 100%. However, there are still districts that do not reach the target of measles immunization (